2008
DOI: 10.1158/0008-5472.can-08-1128
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Doppler Optical Coherence Tomography as a Local Tumor Necrosis Predictor in Photodynamic Therapy of Prostatic Carcinoma: AnIn vivoStudy

Abstract: We have tested the feasibility of real-time localized blood flow measurements, obtained with interstitial (IS) Doppler optical coherence tomography (DOCT), to predict photodynamic therapy (PDT)-induced tumor necrosis deep within solid Dunning rat prostate tumors. IS-DOCT was used to quantify the PDT-induced microvascular shutdown rate in s.c. Dunning prostate tumors (n = 28). Photofrin (12.5 mg/kg) was administered 20 to 24 hours before tumor irradiation, with 635 nm surface irradiance of 8 to 133 mWcm À2 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…However, several groups have shown that an OCT probe may be miniaturized and encased in a medical needle (19,20). Such an imaging probe could be used interstitially to image lymph nodes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, several groups have shown that an OCT probe may be miniaturized and encased in a medical needle (19,20). Such an imaging probe could be used interstitially to image lymph nodes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…6 For instance, Doppler OCT (DOCT) has been used to monitor vascular changes caused by photodynamic therapy. 7 However, it remains challenging to obtain in situ information without resorting to window chamber-implanted tumors due to motion artifacts. In this study, we overcome this challenge with realtime motion gating using speckle variance (SV) imaging.…”
mentioning
confidence: 99%
“…For technical reasons, the microvessel density could only be determined for post-PDT tumor tissue because removing a portion of the tumor before PDT would cause bleeding, interfering with the blood flow measurements. As previously already demonstrated, an accurate measure for vasculature shutdown is the change in microvessel density [10,17,19,[54][55][56][57][58][59][60][61][62].…”
Section: Resultsmentioning
confidence: 89%